Chapter 3: Variety Selection - Donald N. Maynard; Stephen M. Olson (EDIS, 2019)
Selection of the variety to plant is one of the most important decisions the commercial vegetable grower must make each season. This document is HS712, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.